Perancangan Modular Panel dengan Memanfaatkan Limbah Kayu Pinus Bekas - Meilita Tantoroputri; Adi Santosa; Jean Francois Poilot (Intra, 2018)
The dearth of some popular wood species phenomenon is actually inversely proportional with wood growing age. Potential pinewood which is widely available, often used for short-term needs; for example as containers. Therefore, pine waste become increase. This problem is not balanced because there is only a small number of craftsmen who could process it into an attractive product. This situation caused pine waste price become fairly cheap. To overcome this phenomenon, the designer designs modular panels as interior products by utilizing pine waste from containers. The design is based on “Eco-Sustainability